Comparison and Analysis of Timbre Fusion for Chinese and Western Musical Instruments - Liu, Jingyu; Wang, Shuang; Xiang, Yanyin; Jiang, Jian; Jiang, Yujian; Lan, Jing (Frontiers in Psychology, 2022)
Timbre fusion is the theoretical basis of instrument acoustics and Chinese and Western orchestral acoustics. Currently, studies on timbre fusion are mainly focused on Western instruments, but there are some studies on the timbre fusion of Chinese instruments. In this paper, the characteristics of timbre fusion for Chinese and Western instruments are explored, focusing on the subjective attributes and objective acoustic parameters, and a series of experiments is carried out. First, a database containing 518 mixed timbre stimuli of Chinese and Western instruments was constructed to provide basic data that are necessary for the subjective and objective analyses of timbre fusion. We designed and conducted a subjective evaluation experiment of timbre perception attributes based on the method of successive categories. The experimental data were processed using statistical approaches, such as variance analysis, multidimensional preference analysis, and correlation analysis, and we studied the influence of the temporal envelopes and instrument types on fusion, segregation, roughness, and pleasantness. In addition, the differences between Chinese and Western instruments were compared based on these four perception attributes. The results show that fusion and segregation are the most important attributes for Chinese instrument timbre, while roughness is the most important attribute for Western instrument timbre. In addition, multiple linear regression, random forest, and multilayer perceptron were used to construct a set of timbre fusion models for Chinese and Western instruments. The results show that these models can better predict the timbre fusion attributes. It was also found that there are some differences between the timbre fusion models for Chinese and Western instruments, which is consistent with the analysis results of subjective experimental data. The contribution of acoustic objective parameters to the fusion model is also discussed.